Wideband and Ambiguous-Free RF Channelizer Assisted Jointly by Spacing and Profile of Optical Frequency Comb - Xuankun Lu; Wei Pan; Xihua Zou; Wenlin Bai; Peixuan Li; Lianshan Yan; Caihong Teng (IEEE Photonics Journal, 2020)
For civil and military applications, the ability to instantaneously capture and process wideband RF (radio-frequency) signal is of great importance. In this paper, a novel photonics-assisted RF channelized receiver aiming for instantaneous broadband RF signal reception is proposed and experimentally demonstrated. The channelizer is composed of two branches. In one branch, an optical frequency comb (OFC) is generated through a phase modulator (PM), while in the other the optical carrier is frequency-shifted via a polarization modulator (PolM) and then modulated by the captured unknown RF signal. Next, the frequency information of the unknown signal is derived from the frequency sum and the power difference of two specific beating tones, while the incorporation of the comb spacing and the amplitude profile of the OFC enable resolving the ambiguity cases. In the experiments, four receiving channels are constructed using five selected comb lines. The reception and analysis of several RF signals including single-tone, multi-tone and linear frequency modulation (LFM) ones within 1-40 GHz are experimentally validated, which can be extended up to 72 GHz in theory. The proposed channelizer is characterized with ambiguous-free capability, low measurement errors less than 2 MHz, and an SFDR of ∼92 dB·Hz2/3.